Pyometra Presented With Rectal Pain, a Case Report and Review of Literature - Jarjees, Yosra T. (Journal of the Faculty of Medicine Baghdad, 2011)
Pyometra is an uncommon gynecological condition resulted from occlusion of the cervix usually by a malignant condition. It has an incidence of 0.1%-0.5%. Untreated pyometra leads to rupture uterus and acute infective peritonitis presented as acute abdomen and needs urgent surgical intervention. Pyometra resulted from occlusion of the vagina is very rare. No cases have been described in the English literature to the best of our knowledge and in the PubMed. The purpose of reporting this case is to show that occlusion of the vagina could occur in postmenopausal women as a consequence of local infection and results in pyometra and also to show that pyometra can be presented in a different way apart from the classical presentation. The way to reach the diagnosis and how to manage the case has been also discussed thoroughly.